Enhancing the Sensitivity of Power Transformer Differential Protection in Power Systems. - Aso Farooq Hayder; Ismael Kareem Saeed (Zanco Journal of Pure and Applied Sciences, 2025)
Differential protection is a fundamental protection scheme used to detect and isolate internal faults in power transformers. It works on the principle of comparing the currents entering and leaving the protected zone (transformer). Under normal operating conditions or external fault, the current flowing into the transformer should equal the current flowing out, with taking into consideration the transformer’s turn ratio. Under normal conditions, the differential current between primary and secondary sides should be close to zero, a small difference value may exist due to transformer magnetizing current, current transformer (CT) measurement errors and Tap changer position. The Tap changer position will cause the transformer turn ratio errors which is a cause to give trip signal from differential relay to the transformer circuit breaker if it is not compensating in the differential protection relay. Using the new technique of on-load tap changer (OLTC) position to reduce the turn ratio error in order to improve the differential protection sensitivity, the proposal technique includes new equations that are simulated by PSCAD/EMTDC software. It can be clearly shown that the proposed technique will reduce the turn ratio error to the minimum value with comparing to the conventional schemes.